Clinical effectiveness of primary prevention implantable cardioverter-defibrillators: results of the EU-CERT-ICD controlled multicentre cohort study. (6th May 2020) - Zabel, Markus; Willems, Rik; Lubinski, Andrzej; Bauer, Axel; Brugada, Josep; Conen, David; Flevari, Panagiota; Hasenfuß, Gerd; Svetlosak, Martin; Huikuri, Heikki V; Malik, Marek; Pavlović, Nikola; et al.
Abstract: Aims: The EUropean Comparative Effectiveness Research to Assess the Use of Primary ProphylacTic Implantable Cardioverter-Defibrillators (EU-CERT-ICD), a prospective investigator-initiated, controlled cohort study, was conducted in 44 centres and 15 European countries. It aimed to assess current clinical effectiveness of primary prevention ICD therapy. Methods and results: We recruited 2327 patients with ischaemic cardiomyopathy (ICM) or dilated cardiomyopathy (DCM) and guideline indications for prophylactic ICD implantation. Primary endpoint was all-cause mortality. Clinical characteristics, medications, resting, and 12-lead Holter electrocardiograms (ECGs) were documented at enrolment baseline. Baseline and follow-up (FU) data from 2247 patients were analysable, 1516 patients before first ICD implantation (ICD group) and 731 patients without ICD serving as controls. Multivariable models and propensity scoring for adjustment were used to compare the two groups for mortality. During mean FU of 2.4 ± 1.1 years, 342 deaths occurred (6.3%/years annualized mortality, 5.6%/years in the ICD group vs. 9.2%/years in controls), favouring ICD treatment [unadjusted hazard ratio (HR) 0.682, 95% confidence interval (CI) 0.537–0.865, P = 0.0016]. Multivariable mortality predictors included age, left ventricular ejection fraction (LVEF), New York Heart Association class <III, and chronic obstructive pulmonary disease. Adjusted mortality associated with ICD vs. control was 27% lower (HR 0.731, 95% CI 0.569–0.938, P = 0.0140). Subgroup analyses indicated no ICD benefit in diabetics (adjusted HR = 0.945, P = 0.7797, P for interaction = 0.0887) or those aged ≥75 years (adjusted HR 1.063, P = 0.8206, P for interaction = 0.0902). Conclusion: In contemporary ICM/DCM patients (LVEF ≤35%, narrow QRS), primary prophylactic ICD treatment was associated with a 27% lower mortality after adjustment. There appear to be patients with less survival advantage, such as older patients or diabetics.